Pharmacological inhibition of all known major inward cationic currents does not block the induction of spreading depolarizations - Withers, Preston C.; Jones, Allen; Afran-Okese, Kojo Bawuah; Calder, Bailey; Morrill, Hunter J.; Shafer, T. Luke; Nevers, Dallin S.; Norby, Jacob H.; Acosta, Rebeca; Bikman, Benjamin T.; Suli, Arminda; Parrish, R. Ryley (Frontiers in Cellular Neuroscience, 2025)
Spreading depolarization (SD) is a wave of profound cellular depolarization that propagates primarily across gray matter of central nervous system tissue and causes a near-complete collapse of ionic gradients. Implicated in neuropathologies including seizures, migraine with aura, traumatic brain injury, and stroke, SD is experimentally induced in animals by electrical stimulation, mechanical injury, hypoxia, elevated extracellular potassium, and various other techniques. Despite extensive research, the mechanisms underlying SD initiation remain unclear. Prior research in rodents found that simultaneously blocking sodium, calcium, and glutamatergic (AMPA and NMDA) channels prevents SD induction whereas inhibiting any two of these three currents is insufficient. This suggests that SD induction could be a product of overstimulation of any single known inward cationic current. However, some researchers propose that SD induction occurs via an unknown “SD channel.” To further explore the role of known inward cationic currents in SD induction, we applied high potassium to two biological models, namely zebrafish and mice. First, we developed a novel ex vivo zebrafish model to assess SD induction in the optic tectum. Using KCl microinjection and DC recordings, we found that inhibition of sodium, calcium, and glutamatergic channels significantly decreased SD amplitude but never blocked SD induction in the zebrafish optic tectum. Similar pharmacological experiments in hippocampal mouse slices (CA1 subregion) also confirmed that SDs persist despite the same pharmacological cocktail. These findings suggest that additional mechanisms beyond sodium, calcium, and glutamatergic signaling contribute to SD induction, supporting the hypothesis that an unknown channel is critical in SD physiology.